Analysis of the Influence of Cultural Factors on Consumer Preferences in Product Purchasing Decisions: A Cross-Cultural Study of the Global Market - Herdiyanti Herdiyanti; Ansir Launtu; Betty Rahayu; Wahyu Surya Putra S; Chairul Anam (Dinasti International Journal of Education Management And Social Science, 2024)
This article delves into the intricate relationship between cultural factors and consumer preferences, focusing on their impact on product purchasing decisions in the global market. Through a comprehensive literature review, various cultural dimensions such as values, beliefs, norms, and traditions are examined for their influence on consumer behavior. The analysis encompasses diverse cultural contexts, highlighting the significance of understanding cultural nuances in shaping consumer preferences. The findings reveal a complex interplay between culture and consumer choices, indicating that cultural factors significantly shape individuals' perceptions of products and brands. Moreover, this cross-cultural article underscores the need for businesses to adopt culturally sensitive marketing strategies to effectively target and engage diverse consumer segments worldwide.